XVIII. Yüzyılda Avusturya'da Alla-Turca Anlayışı ve Buna Etki Eden Unsurlar - İstek, Emrah (Muş Alparslan Üniversitesi, 2020)
The contact between theOttoman Empire and Austria XVI. century, XVIII. Century until a seriouscultural interaction can not be mentioned. In the 18th century, both countriestried to seek a treaty ground with each other, the Ottoman Empire senttemporary envoys to Europe; In order to increase relations with Turks inAustria, factors such as the establishment of the Orient Academy and the spreadof Turkish fashion in the country have increased the interaction. From thebeginning of the 18th century until the end of this period, weddings, paradesand ceremonies food, beverage and clothing culture, architectural structures, musical instruments and musicals made in Austria according to Turkish duly orAlla-Turca concept are important for demonstrating the dominance of Turkishfashion in Austria. Therefore, this study was tried to illustrate theAlla-Turca flow in Austria and was added to the end of the 18th century studyto base the research on concrete data.

Osmanlı Devletiile Avusturya’nın birbiri ile teması XVI. yüzyılda başlasa da, XVIII. yüzyılakadar kültürel anlamda ciddi bir etkileşimden bahsedilemez. XVIII. yüzyılda iseher iki ülkenin birbiriyle antlaşma zemini arama çabası, Osmanlı Devleti’ninAvrupa’ya geçici elçiler göndermesi; Avusturya’da Türklerle ilişkilerinartırılması için Şark Akademisinin kurulması ve Türk modasının ülke içerisindeyayılmaya başlaması gibi etkenler karşılıklı etkileşimi artırmıştır. XVIII.yüzyıl başlarından sonuna kadar Avusturya’da Türk usulüne uygun veya daAlla-Turca anlayışına özgü yapılan düğünler, resmigeçitler ve merasimler, yiyecek, içecek ve giyecek anlayışı ile mimari yapılar, müzik aletleri vemüzikaller, Türk modasının Avusturya’daki hâkimiyetini göstermesi açısındanönemlidir. Bu nedenle bu çalışmada Avusturya’daki Alla-Turca akımı örneklerlegösterilmeye çalışılmış ve araştırmayı somut verilere dayandırmak amacıylaXVIII. yüzyıla ait görseller çalışmanın sonuna eklenmiştir.
The Perception of Alla-Turca in Austria in the 18th Century and Its Impacted Elements
anemon
Keywords: Alla-Turca; Turkish Fashion; Ottoman Empire; Austria; 18th Century; Alla-Turca; Türkenmode; Osmanlı Devleti; Avusturya; XVIII.Yüzyıl